Enhanced Performance of Carbon–Selenide Composite with La0.9Ce0.1NiO3 Perovskite Oxide for Outstanding Counter Electrodes in Platinum-Free Dye-Sensitized Solar Cells; Nanomaterials; Vol. 12, iss. 6 - Tapa A. R. Arnauld Robert; Xiang Wanchun; Wu Senwei; Li Bin; Liu Qiufen; Zhang Mingfeng; Ghadamyari Marzieh; Verpoort F. V. K. Frensis Valter Kornelius; Wang Jichao; Trokourey Albert; Zhao Xiujian (2022, 2022)
Title screen